MONOTONE FAMILIES ON CYCLIC SEMIGROUPS - Гаврилків, Володимир Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Given a cyclic semigroup S we study right and left zeros, singleton left ideals, the minimal ideal, central elements, left cancelable and right cancelable elements of extensions υ (S ) and characterize cyclic semigroups whose superextensions are commutative.